(untitled) (American Journal of Interdisciplinary Research and Development, 2022)
The article describes the specific principles of organizing a competence-oriented educational process in the preparation of future biologists for professional activities. Focusing on the process of competence-oriented learning, the essence of the principles of professional development, the activation of students, scientific character, and the relationship between theory and practice are highlighted.